Effectof adding of vitamin b12 to tris extender and cooling period on the sperms viablilty for awassi rams - Shehab Ahmed, Ali (Journal of Kerbala for Agricultural Sciences, 2017)
A study was conducted to investigate the effect adding B12 to tris extender on the physical and chemical semen characteristics, the semen storage at (5°C).five Awassi rams 3-4 years of age all semen samples were tested for physical characters such as(individual motility ,live and dead sperm ,abnormal sperm%, ,Hypoosmotic test %, ALT and AST). Semen from each rams in the groups were pooled and divided into four parts to study the effect of adding different concentrations of antioxidants B12 to the diluent of semen .The added B12, was (0,1,2,3 mg\ml) , Semen diluent were kept in refrigerator (5°C). The results showed that there were significant differences between the concentration (2,3, mg\ml) B12 comparison to(0,1mg\ml) B12 in individual motility 3.00 ± 78.42 , 2.22 ± 81.13% and 0.19 ± 75.62 , 3.17 ±87.49 in live and dead sperm comparison to control 12 ±73.55 at first day, and Hypoosmotic 0.77 ± 78.66 ,1.37 ± 81.33 comparison to control 0.45 ± 62.54ALT and AST , 0.49 ± 27.81 ,1.19 ± 26.29 comparison to control1.34 ± 33.53 % at third day and there were significant differences between the concentration (2,3, mg\ml) B12 comparison to(0,1mg\ml) in all characters at fifth day.